The mechanism of anger and negative affectivity on the occurrence of deviant workplace behavior: An empirical evidence among Malaysian nurses in public hospitals - Maslina Mansor; Rashidah Mohd Ibrahim; Asyraf Afthanorhan; Ahmad Munir Mohd Salleh (Belitung Nursing Journal, 2022)
Background: Employees’ work experience significantly impacts their cognition and workplace actions. Anger and negative affectivity are two personality traits that have been linked to workplace deviant behavior conduct. Objective: This study aimed to empirically analyze the deviant workplace behavior and its antecedents among Malaysian nurses in public hospitals. Methods: A cross-sectional design was employed in this study. The survey questionnaires were distributed proportionately to staff nurses in six government hospitals in 2020, with a total of 387 nurses selected using a simple random sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis. Results: Trait anger triggered deviant workplace behavior in Malaysian nurses, thus supporting the argument that the personality trait could increase deviant behavior (β = 0.245, p = 0.000). At the same time, there was no evidence that negative affectivity could influence deviant behavior in the workplace among nurses in selected public hospitals in Malaysia (β = 0.074, p = 0.064). Conclusion: The Malaysian nurses had positive affectivity, related to positive emotions like happiness, work interest, and attentiveness. On the other hand, the nurses were suffering from high levels of emotional tiredness. Further research should highlight a deeper understanding of Malaysian nurses’ work experiences and workplace stress affecting their physical and mental health.